A Qualitative Analysis of Translanguaging by Colombian Migrants in North Carolina - Scott Lamanna (Languages, 2021)
This study examines the usefulness of the theoretical construct of translanguaging in analyzing the linguistic production of twenty-four Colombians (originally from Bogotá) residing in the Piedmont Triad region of North Carolina. Translanguaging maintains that bilinguals and multilinguals have a single linguistic repertoire consisting of features traditionally associated with different named languages (English, Spanish, Arabic, Chinese, etc.), and that they freely select from among these features according to their communicative needs in specific contexts. In terms of named languages, participants utilized varying amounts of English during sociolinguistic interviews conducted primarily in Spanish by the investigator. The study presents a qualitative analysis of participants’ linguistic production viewed through the lens of translanguaging, which offers a better account than codeswitching of several patterns of language use observed in the data. These include phonetically ambiguous words, fluid combinations of morphemes from each named language (Spanish and English), and innovative uses of linguistic forms. The study concludes with a consideration of the relevance of translanguaging in addressing the issue of the legitimacy of the (often stigmatized) language varieties of Hispanics in the U.S. context.